Correlation Between Coupling Metrics Values and Number of Classes in Multimedia Java Projects: A Case Study - Bivde, V S; Sarasu, P (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2021)
Coupling is an interdependence relationship between the modules of object-oriented software. It is a property with the most influence on quality attributes of the object-oriented software. Coupling with high values results in complex software design hence software professionals try to keep the coupling as low as possible. The values of coupling metrics are dependent on the type of input source code. Reusability is the main feature of object-oriented languages, so coupling occurs due to reuse of code modules. This paper investigates a correlation between the values of coupling metrics and the number of classes in the multimedia Java code. Here, a case study of a banking multimedia Java project with its forty different versions is conducted to comments on this correlation. The analysis of the results shows that, if the input source code is with a large number of classes then it results in high coupling values.
Keywords: objects; software; class; java; project management; IJIMAI